X linked hydrocephalus: a survey of a 20 year period in Victoria, Australia. Issue 1 (February 1986) - Halliday, J; Chow, C W; Wallace, D; Danks, D M
Abstract : This study ascertained 164 males with non-communicating hydrocephalus in live or stillborn patients in Victoria. Australia in 1962 to 1982, after excluding those cases secondary to brain malformations other than aqueduct stenosis. Ascertainment was considered near complete, especially for the period since 1974, but details of the aqueduct pathology were inadequate in half the cases. A total of 91 families was seen to record detailed family information. The overall incidence of primary non-communicating hydrocephalus was estimated to be 0.6 +/- 0.2 per 1000 live and stillbirths, with three-fifths of the cases male. Twelve patients were classified as having definite X linked hydrocephalus and 13 others as probable cases of this condition. Deformities of the thumbs (generally adduction deformity) were present in nearly half of these cases. The pyramids were absent from sections of the medulla whenever these were available. Four of five survivors had signs suggesting pyramidal tract lesions, compared to four of 25 surviving non-X linked cases. The intellectual outcome was notably poorer in the X linked cases. Poor school performance was also described in five of 19 mothers of X linked cases but in only one of 64 mothers of the remaining cases. Familial recurrence in the whole group of patients was almost confined to the X linked families. The exceptions were two families in whom autosomal recessive inheritance is possible. It is important to remember X linked hydrocephalus in genetic counselling. Examination of the thumbs, search for clinical signs of pyramidal tract lesions, and anatomical examination of the pyramids in medullary sections are all important, along with careful questioning for a history of affected maternal relatives. The presence of any of these features is grounds for counseling on the basis of X linked inheritance. An empirical figure was derived to use when counseling about a male with non-communicating hydrocephalus in whom there is no adequate information about the thumbs or the pyramids: a 4% recurrence risk in male sibs and 2% in females.